ANALISIS RASIO KEUANGAN DALAM MEMPREDIKSI PERUBAHAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - SYAHRUL SYAHRUL; SAFRI SAFRI; ESTER NAIBAHO (JURNAL TEKNIK INDUSTRI, 2021)
ABSTRACTThis study aims to determine the effect of liquidity ratios, solvency ratios, profitability ratios and market ratios on earnings predictions. The liquidity ratio is proxied as ITO, the solvency ratio is represented as DAR, the profitability ratio is proxied as GPM and FAT. The market ratio is expressed as EPS & PER. Samples through purposive sampling of 17 companies. Hypothesis testing using multiple regression. The results showed that EPS & PER had a partial effect on changes in earnings. Meanwhile, ITO, DAR, GPM & FAT do not affect partially on changes in profits. Keywords: Liquidity Ratio, Solvency, Profitability, Market Ratio.